Regular inhaled beta agonist in asthma: effects on exacerbations and lung function. - Taylor, D R (1993)
BACKGROUND: A comparison of the effects of regular upsilon as needed inhaled beta agonist treatment on the control of asthma in the last 16 weeks of each of two 24 week treatment periods has been reported. This paper presents additional information on exacerbations of asthma and trends in lung function, airways hyperresponsiveness to methacholine, and bronchodilator responsiveness during the entire 24 week periods of regular or as needed beta agonist treatment. METHODS: Subjects undertook a year long randomised, double blind crossover study of regular upsilon as needed inhaled beta agonist treatment. Fenoterol (400 micrograms) or matching placebo was inhaled as a dry powder four times daily for 24 weeks, then subjects crossed over to the alternative regimen. Treatment with inhaled corticosteroids was used by 50 of the 64 subjects in constant doses throughout the study. Symptoms, peak expiratory flow rates, and drug use were recorded daily, spirometry was performed every four weeks, and methacholine and bronchodilator responsiveness were measured every eight weeks. RESULTS: Exacerbations of asthma symptoms occurred earlier and more often during regular treatment with fenoterol and four of five severe exacerbations requiring admission to hospital occurred during the period of regular treatment. Prebronchodilator forced expiratory volume in one second (FEV1) was on average 0.15 litres lower (95% confidence interval (95% CI) 0.11-0.19) and vital capacity (VC) 0.12 litres lower (95% CI 0.08-0.16) than during the placebo period. Morning peak flow rates were significantly lower and evening peak flow rates significantly higher, with an increase in diurnal variation from 9.8% (95% CI 6.9-12.8) to 17.5% (95% CI 13.8-21.3) during regular treatment. Geometric mean concentration of methacholine causing a 20% fall in FEV1 from the value after saline (PC20) decreased significantly from 1.63 to 1.15 mg/ml, indicating increased bronchial hyperresponsiveness during regular treatment. Response to bronchodilator, as measured by the % increase in postbronchodilator FEV1 related to prebronchodilator FEV1, was maintained with no evidence for tachyphylaxis. CONCLUSION: Chronic use of inhaled fenoterol resulted in more exacerbations, a significant decline in baseline lung function, and an increase in airway responsiveness to methacholine in asthmatic subjects, but did not alter bronchodilator responsiveness. These findings support the previous report that regular inhaled beta agonist treatment is deleterious in the long term control of asthma.